Partnership for Growth : Linking Large Firms and Agro-Processing SMEs - World Bank Group (World Bank, Washington, DC, 2018)
Partnership for growth: linking large firms and agro-processing small and medium enterprises (SMEs) presents lessons learned from various models utilized by public and private sector programs to stimulate the growth of agro-processing SMEs through linkages to larger firms in developing countries. The study serves as a reference for policymakers, development practitioners, and private sector actors. It used a three-pronged approach to data collection, analysis, and synthesis. First, a literature review was conducted to identify results and outcomes of recently implemented lead firm - SME linkage programs. Second, the literature review helped identify examples of initiatives focused on linking lead firms and agro-processing SMEs in 56 countries in Africa, Asia, Eastern Europe, and Latin America. Data from 66 projects were examined in a meta-analysis to refine the findings from the literature review. Third, six linkage initiatives with a broad range of projects in numerous locations were selected for in-depth analysis and inclusion in the report as case studies. The guidance note for policy makers aims to provide guidance to policymakers hoping to promote the growth of agro-processing SMEs by positioning them as suppliers to larger firms. The six case studies are intended to provide development practitioners with further details and contextual insights, which they can consider when designing lead firm - SME linkage programs.